2014
DOI: 10.1530/eje-14-0225
|View full text |Cite
|
Sign up to set email alerts
|

Secular trends in the prognostic factors for papillary thyroid cancer

Abstract: Objective: With the recent increasing rates of screening for thyroid cancer, the cancers now tend to be smaller and less aggressive than those that are diagnosed when presented with symptoms, suggesting changes in the clinical validity of conventional prognostic factors for outcomes. We performed the retrospective study to identify the secular trends in the prognostic factors of thyroid cancer. Methods: We used medical records of 3147 patients diagnosed with papillary thyroid cancer (PTC) at the Seoul National… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…In recent years, the incidence of small thyroid cancer has increased globally mainly as a result of thyroid ultrasound screening . Consistent with this, changes over time in clinicopathological characteristics, outcomes and prognostic factors for differentiated thyroid cancer (DTC) have been reported. In a similar manner, increases in thyroid screening with ultrasound and measurement of serum calcitonin in subjects with thyroid nodules might have led to earlier detection of smaller MTCs.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…In recent years, the incidence of small thyroid cancer has increased globally mainly as a result of thyroid ultrasound screening . Consistent with this, changes over time in clinicopathological characteristics, outcomes and prognostic factors for differentiated thyroid cancer (DTC) have been reported. In a similar manner, increases in thyroid screening with ultrasound and measurement of serum calcitonin in subjects with thyroid nodules might have led to earlier detection of smaller MTCs.…”
Section: Introductionmentioning
confidence: 69%
“…LNs were also assessed based on positive or negative LNs, and nonresected LNs were categorized as negative LNs. Genetic tests for RET proto-oncogene mutation (exons 8,10,11,13,14,15,16), which was start to implement frequently since 2008, were performed in 172 patients, and family history of MTC or the presence of phenotypes of multiple endocrine neoplasia type 2 (MEN2) was obtained by reviewing the medical records for 310 patients. To evaluate changes in pathological findings over time, the patients were classified into four groups based on the year of diagnosis: This study was conducted in accordance with the principles of the Declaration of Helsinki and was approved by the Institutional Review Board of SNU Hospital (IRB No.…”
Section: Patient Selectionmentioning
confidence: 99%
“…The overall median follow‐up duration was 4.8 years (interquartile range, 3.4‐10.6 years). The treatment protocol was the same as that in previous studies . The high‐risk group of the ATA staging system was defined by the presence of any of the following: macroscopic tumor invasion, incomplete tumor resection, and distant metastasis.…”
Section: Methodsmentioning
confidence: 99%
“…Third, we included all patients with thyroid cancer rather than only differentiated thyroid cancer, which might benefit from RAIT after thyroid surgery because the NHI database did not have information on histopathology. However, a recent Korean report regarding the histological classification of thyroid cancer showed that over 98% of new cases of thyroid cancer are patients with differentiated thyroid cancer (2,39); therefore, this limitation should have little effect on the study results.…”
Section: Figmentioning
confidence: 98%